A Comparison of Test Procedures for Estimating the Bond Ball Work Index on Zambian/DRC Copper–Cobalt Ores and Evaluation of Suitability for Use in Geometallurgical Studies - Elizma Ford; Vincent Sithole (The Southern African Institute of Mining and Metallurgy, 2015)
"Two shortened test procedures for estimating the Bond ball work index are compared for suitability of use on Zambian/DRC-type copper–cobalt ores. The first procedure is based on a batch milling test while the second procedure is based on a limited locked-cycle test. Both procedures were conducted using a standard Bond test mill. INTRODUCTION The Bond ball work index is widely used in the field of minerals processing as an indicator of ore grindability. The work index is determined by means of a locked-cycle test procedure that typically requires seven to eight cycles to stabilise at a re-circulating load of 250%. A typical test requires between three to four kilogram of ore sample and around eight hours of operator time. For geometallurgical test work applications, where a large number of variability samples are to be tested, it would be highly beneficial to use a test procedure that requires less sample mass and operator time. Certain test work laboratories, for example SGS and JK Tech, are already offering various types of shortened test procedures for estimating the Bond ball work index. This paper discusses a comparison of two shortened test procedures that were evaluated for suitability of use on Zambian/DRC-type copper–cobalt ores. EXPERIMENTAL Test Procedure 1 – Batch Milling The first test procedure is derived from a batch milling approach proposed by the University of Hacettepe (Aksani, 2000). Some modifications were, however, made to the data analysis method from that originally proposed. During this test procedure, a 700 mL volume of sample is milled in a standard Bond test mill for a pre-determined number of revolutions. The feed and product particle size distributions are measured for each test. These results are then used to back-calculate a cumulative breakage rate parameter (k) for each particle size, according to the following formula:"